1994
DOI: 10.1002/mrd.1080380113
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular signal transduction mechanisms of rat epididymal spermatozoa and their relationship to motility and metabolism

Abstract: The role of intracellular signal transduction mechanisms in regulating the motility and metabolism of rat spermatozoa in undiluted caudal epididymal fluid (CEF) was examined. Samples of CEF containing immotile spermatozoa were exposed to drugs and other agents that either stimulate signal transduction pathways or mimic the action of their second messengers. Under these conditions, sperm motility in 25-30 nl of CEF was stimulated by calcium ions (Ca2'), N2,2'-0-dibutyrylguanosine 3':5'-cyclic monophosphate (dib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 32 publications
5
33
0
Order By: Relevance
“…Pentoxifylline inhibits cAMP phosphodiesterase, thus increasing the intracellular cAMP concentration (Garbers et al 1971). A rise in cAMP concentration causes an increase in the cAMP-dependent processes of spermatozoa such as motility, capacitation and acrosome reaction in spermatozoa (Armstrong et al 1994, Aitken 1997). …”
Section: Introductionmentioning
confidence: 99%
“…Pentoxifylline inhibits cAMP phosphodiesterase, thus increasing the intracellular cAMP concentration (Garbers et al 1971). A rise in cAMP concentration causes an increase in the cAMP-dependent processes of spermatozoa such as motility, capacitation and acrosome reaction in spermatozoa (Armstrong et al 1994, Aitken 1997). …”
Section: Introductionmentioning
confidence: 99%
“…There is general agreement that the cyclic nucleotide adenosine 3 ,5 -cyclic monophosphate (cAMP) plays a role in regulating sperm function, including motility and there is also evidence to suggest that an increase in cAMP is associated with activation of motility in spermatozoa from the cauda epididymidis of hamsters (Morton et al, 1974) and rats (Armstrong et al, 1994). Ca 2+ also activates motility in spermatozoa from the cauda epididymidis from both these species (Morton et al, 1974;Armstrong et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Ca 2+ also activates motility in spermatozoa from the cauda epididymidis from both these species (Morton et al, 1974;Armstrong et al, 1994). …”
Section: Introductionmentioning
confidence: 99%
“…One possibility might be the involvement of cAMP signal transduction pathways. It has been reported that these pathways are involved in activation of sperm motility (Armstrong et al, 1994;Wade et al, 2003). This increase in motility is an important factor affecting fertilization, because high rates of ovum fertilization require efficient transport of sperm from the cervix to the oviducts (Hawk et al, 1978).…”
Section: Discussionmentioning
confidence: 99%